SOSIALISASI PROGRAM BANTUAN STIMULAN PERUMAHAN SWADAYA (BSPS) UNTUK RUMAH LAYAK HUNI DI KOTA PALEMBANG - Pusnita, Indah; Wagisri, Wagisri; Tessa, Juliah; Nurwahyuliningsih, Eka; Dewi, Inne Miftah (Aktivasi: Jurnal Pemberdayaan Masyarakat, 2025)
Decent housing is a fundamental need that plays a crucial role in improving community welfare. However, many families, particularly low-income households (MBR), face challenges in accessing housing that meets health, safety, and comfort standards. To address this issue, the government, through the Ministry of Public Works and Housing (PUPR), launched the Self-Help Housing Stimulant Assistance Program (BSPS) to improve access to adequate housing for MBR. This article discusses the implementation of the BSPS program's socialization in Kota Palembang as a strategy to enhance public understanding and participation in the program. The methods used in this activity include socialization, verification of aid recipients, and technical assistance in house renovation or construction. The findings indicate that intensive socialization plays a vital role in raising community awareness about the benefits and mechanisms of the BSPS program. Additionally, the formation of Beneficiary Groups (KPB) helps manage aid in a transparent and effective manner. Active community participation in each stage of the program is also a key factor in its success. Through the BSPS program, low-income communities are expected to gain access to better housing and improve their quality of life. Recommendations from this study include broader socialization efforts, strengthening KPB capacity, and continuous evaluation to ensure the program's long-term impact on community welfare.